An energy allocation based design approach for flexible rockfall protection barriers. (15th October 2018) - Xu, Hu; Gentilini, Cristina; Yu, Zhixiang; Qi, Xin; Zhao, Shichun
Highlights: Several experimental tests are conducted on barrier components and on a full-scale rockfall barrier prototype. Reliable numerical models of rockfall barriers are calibrated employing the rich set of experimental data. The total energy distribution during impact among the barrier components is analyzed. A quick and reliable design procedure for rockfall barriers is presented. The procedure is assessed with an additional full-scale impact test on a rockfall barrier prototype. Abstract: This paper proposes an effective design approach for quickly determining the specification, size and amount of components of a flexible rockfall protection barrier structure. The approach is based on a reliable numerical modelling validated by several experimental tests that include both component tests and full-scale impact tests. The interception structure made up of a steel wire-ring net is accurately investigated through a series of in-plane and out-of-plane quasi-static tests carried out on net specimens, to define the ring constitutive model and failure criterion. The accuracy of the numerical strategy for an overall barrier structure with nominal energy level of 1500 kJ is validated by a full-scale in-situ test including service energy level (SEL) and maximum energy level (MEL) impacts, according to the European guidelines. From the numerical models, it is inferred that the total energy of the impact is simultaneously dissipated in different ways, where the internal energy of the structure plays a significant role. The distribution of the absorbed energy among the different barrier components is explored and defined by means of the developed finite element model. Besides, the design values of the internal force in the ropes are derived with an adequate safety margin. The proposed design procedure, applied to a barrier structure with nominal energy level of 3500 kJ, is assessed by a full-scale impact test, proving that the design approach is reliable and efficient.